JACINDA ARDERN’S SPEECH ANALYSIS FROM LINGUISTIC AND PEDAGOGICAL PERSPECTIVES - Alamsyah, Aam; Gustary, Devian; Muji, Windika (ReALL - Research on Applied Linguistics and Literature, 2023)
The research aims to comprehend the use of deictic expressions in Jacinda Ardern’s speech and identify the potential use of the deictic expressions in the EFL context. The present study was conducted qualitatively. The researchers identified the sources of data manually. They further identified the data sources by watching the YouTube channel containing the speech performed by Jacinda, who was once a newly elected prime minister. The findings indicated that the person’s deixis is the most frequently used in her speech. For example, ‘we’ is the most frequent pronoun to indicate the sense of togetherness between the speaker and her audience. In terms of the application of personal deixis in the pedagogical context, it can also be found that the use of personal deixis belongs to the most frequently used deictic expression by teachers. Despite its importance, the use of personal pronouns in English learning process can pose a persistent problem to non-native English learners, as English is known as the language which emphasizes the harmony between subject and verb. The researchers suggest that the teaching of pronouns be conducted in more contextually meaningful approaches. Keywords: Jacinda Ardern, Speech, Linguistic, Pedagogy